Comparative Evaluation of Healing Outcomes Following Endodontic Microsurgery Using Bioceramic Versus MTA Root-End Filling Materials. - Singh H, Singh H; De S, De S; Katyan P, Katyan P; Sarkar O, Sarkar O; Mehrotra K, Mehrotra K; Mukherjee S, Mukherjee S (Journal of Neonatal Surgery, 2025)
Background:Endodontic microsurgery is an established treatment modality for persistent periapical lesions when conventional root canal therapy fails. The choice of root-end filling material plays a critical role in achieving optimal healing outcomes. Mineral Trioxide Aggregate (MTA) has long been considered the gold standard, while newer bioceramic materials have demonstrated promising biological and sealing properties. Aim:To compare the clinical and radiographic healing outcomes of MTA and bioceramic root-end filling materials following endodontic microsurgery. Materials and Methods:This randomized clinical study included 30 patients diagnosed with persistent periapical pathology requiring endodontic microsurgery. Participants were randomly assigned into two groups: Group I (MTA, n = 15) and Group II (Bioceramic, n = 15). Clinical and radiographic evaluations were performed at 1 week, 3 months, 6 months, and 12 months postoperatively. Postoperative pain was assessed using the Visual Analog Scale (VAS), while radiographic healing was evaluated using the Periapical Index (PAI). Clinical healing outcomes were categorized as complete healing, incomplete healing, or failure. Statistical analysis was performed using independent t-tests and chi-square tests, with significance set at p < 0.05. Results:Baseline demographic characteristics were comparable between the groups (p > 0.05). Both groups demonstrated progressive reduction in postoperative pain throughout the follow-up period. Mean VAS scores were slightly lower in the bioceramic group at all intervals; however, no statistically significant differences were observed (p > 0.05). Radiographic assessment revealed a significant reduction in PAI scores over time in both groups. At 12 months, the bioceramic group exhibited significantly lower mean PAI scores compared with the MTA group (1.00 ± 0.38 vs. 1.40 ± 0.51; p = 0.027), indicating superior radiographic healing. Complete clinical healing at 12 months was observed in 80.0% of MTA-treated cases and 93.3% of bioceramic-treated cases, although the difference was not statistically significant (p = 0.283). No treatment failures or persistent infections were reported in either group. Conclusion:Both MTA and bioceramic materials were highly effective as root-end filling materials in endodontic microsurgery, resulting in high clinical success rates and favorable periapical healing. While both materials produced comparable clinical outcomes, bioceramic material demonstrated significantly better radiographic healing at 12 months, suggesting a potential advantage in promoting periapical tissue regeneration..